2021
DOI: 10.5194/acp-2021-528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of organic aerosol composition determined by offline FIGAERO-CIMS on particle absorptive properties in autumn Beijing

Abstract: Abstract. Organic aerosol (OA) is a major component of fine particulate matter (PM) affecting air quality, human health, and the climate. The absorptive and reflective behavior of OA components contributes to determining particle optical properties and thus their effects on the radiative budget of the troposphere. There is limited knowledge on the influence of the molecular composition of OA on particle optical properties in the polluted urban environment. In this study, we characterized the molecular composit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Figure shows the relative ion signals grouped by their molecular formulae as well as their carbon and oxygen numbers. A study that was conducted in winter in 2018 in Beijing showed similar molecule compositions except that the relative signal intensities of sulfur-containing ions were smaller in our study (Figure S11 in the Supporting Information) . C x H y O z ·I – ions were the most abundant for all cases, contributing to 60–70% of the total signal intensities in haze-day samples and about 84% in clean-day samples (Figure a–c).…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…Figure shows the relative ion signals grouped by their molecular formulae as well as their carbon and oxygen numbers. A study that was conducted in winter in 2018 in Beijing showed similar molecule compositions except that the relative signal intensities of sulfur-containing ions were smaller in our study (Figure S11 in the Supporting Information) . C x H y O z ·I – ions were the most abundant for all cases, contributing to 60–70% of the total signal intensities in haze-day samples and about 84% in clean-day samples (Figure a–c).…”
Section: Resultssupporting
confidence: 62%
“…The campaign-average mass ratio of nitrate to sulfate was 1.6, which was higher than 0.6–1.4 reported previously for winter Beijing . An even greater ratio of 2.1 was observed in winter in 2018 in Beijing . The increasing nitrate-to-sulfate ratio was consistent with the significant reduction of sulfate and less efficient reduction of nitrate in the NCP …”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations